Exploratory Study: A Modification Training Method of Attentional Bias Toward Safety - Jingqi Gao; Xiang Wu; Xiaowei Luo; Ao Zhang (Elsevier, 2021)
Background: The high sensitivity of individuals toward safety information in production activities, that is, attentional bias toward safety (ABS), can positively predict safe behaviors. It has become a hot topic in current organizational safety behavior research. However, there is no literature on its modification method. Methods: Based on the modified dot-probe task, we designed a modification training method of ABS. The training method required subjects to respond to the location of detection points that presented after safety stimulus and neutral stimulus pictures. Subjects' attentional bias values of safety and neutral pictures were measured during the experiment. Twenty-one students were selected and divided into a control group and training group to gain comparable results. Results: A novel training method was developed in this study to promote the efficacy of safety stimulus by activating ABS of the subjects. Moreover, repeated trainings and preacquired relative knowledge can enhance this effect. Conclusion: This study develops an experimental approach to evaluate the effectiveness of safety education and safety training, and also provides a new research idea for accident prevention.